Online assessment in Moodle: A framework for supporting our students - Padayachee, P.; Wagner-Welsh, S.; Johannes, H. (South African Journal of Higher Education, 2019)
With the increased intake of students at many higher education institutions, the teaching, learning and assessment of large groups is one of the biggest challenges facing educators. Appropriate online assessment may address some of the challenges faced in the teaching and learning setting. In this paper, the experiences of 392 mathematics students, undertaking their assessments via Moodle at a University in the Eastern Cape of South Africa, are described. Student experiences informed the design of a supportive-environmental framework for online assessment. The theoretical lens for this research study is framed by mastery learning, student experience and online assessment. The research reported on in this paper highlights one aspect of the project: the third phase of the action-research cycle, namely, to observe the implementation of online assessment. Examples from two blended-learning Moodle courses highlight some of the experienced difficulties and successes. The lessons learnt informed the online-assessment design and implementation to introduce supportive environments for online assessment. The knowledge gained from this study culminated in a 4-Pillar Supportive-Online Assessment Framework for Blended-Learning environments, which could contribute to an improvement in online-assessment practices.